Performance of carbide tools coated with DLC in the drilling of SAE 323 aluminum alloy - Silva, W. M. [UNESP]; Jesus, L. M.; Carneiro, J. R.; Souza, P. S.; Martins, P. S.; Trava-Airoldi, V. J. (Elsevier B.V., 2015)
The development of new coatings in the last years contributed to the improvements of machining industry. In general, it is known that the performance of drilling tools increases with the application of a proper coating, and it is worth remembering that the adhesion is an important condition for the success of any coating. This work presents a performance of cemented carbide cutting tool coated with diamond-like carbon (DLC). The deposition of the coating used in this study has been done using plasma enhanced chemical vapor deposition system. Suitable adhesion between film and the substrate did not occur in the initial deposition parameters tested. To enhance adhesion of the film, an intermediate silicon layer has been added. To evaluate this adhesion, VDI 3198 standard adhesion test was used. Spectra analyses collected using Raman backscattering spectroscopy have been used to characterize the composition and structural information of the film. The silicon layer was evaluated using atomic force microscopy. Drilling tests were performed using workpieces casting in aluminum alloy (SA-323) and roundness, radial deviation, deviation of diameter and roughness of geometries changes were measured as a function of the number of holes produced. The results showed that the DLC coating improves the tool performance, which subsequently improves the drilling quality. (C) 2015 Elsevier B.V. All rights reserved.
Keywords: Coating; Diamond-like carbon; Silicon; Adhesion; Tool; Drilling